Kinetically Stable Oxide Overlayers on Mo3 P Nanoparticles Enabling Lithium-Air Batteries with Low Overpotentials and Long Cycle Life - Kondori, Alireza (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 Wiley-VCH GmbH.